Attitudes and Beliefs of Midwifery Students on Sexuality and Evaluation of Sexuality: A Mixed-Method Study - Basgol, Sukran; Bal, Sümeyye; Keten Edis, Elif; Koç, Emine; Çokyeter, Büşra (Shahroud Journal of Medical Sciences, 2024)
Background: The sexual attitudes and beliefs of midwifery students, who play an important role in improving sexual health, can affect both the students themselves and people with disabilities to whom they provide education and counselling. This study aimed to determine the attitudes and beliefs of midwifery students on sexuality and the evaluation of sexuality.Methods: This research is a mixed-method study that includes two stages: qualitative and quantitative. In the first stage, data was collected from 334 students using a socio-demographic data form and the sexual attitude and belief scale. The second stage involved conducting phenomenological interviews with 21 students.Results: The students who believed they had adequate knowledge about sexuality and reproductive health, as well as those who had previously engaged in scientific activities related to sexuality, held more positive attitudes and beliefs towards sexual care. The qualitative section of the study identified four main themes, each containing 13 sub-themes, which provided further insights into the students' perspectives on the subject.Conclusions: The students acknowledged that their society had strict sexual taboos, but their attitudes toward sexuality changed after studying sexual health and women's health at university. The study highlighted the challenges faced by midwifery students in assessing sexual health. By addressing these difficulties, trained midwives can better evaluate the sexual health of patients in clinical settings, leading to early detection of sexual problems.Keywords: Sexuality, Sexual health, Sex education